KOMUNIKASI BERPENGARUH TERHADAP EFEKTIVITAS PELAYANAN ADMINISTRASI KEPENDUDUKAN - Yulianus Rusdi E.42008045 (FISIP Universitas Tanjungpura Pontianak, 2012)
This paper writing slated for menganalisis communication influence to demography administrative services effectiveness at Camat Samalantan's Office Gorged Regency. This research utilizes quantitative method, This research did by advance research steps, making observational plan, making kuesioner and tests kuesioner's validity, primary downloading and secondary, doing analisis data and makes research reporting (paper). Observational location at Camat Samalantan's Office. Observational sample is Babane's Silvan society. This observational result show that camat's communication less effective and demography administrative services effectiveness also effective reducing. Meanwhile camat's communication contribution to demography administrative services effectiveness just as big as 13,18 % and as more as it regarded by other variables that don't be worked through deep observational it. Conclusion in observational it is communication influentialing to demography administrative services effectiveness at Camat Samalantan's Office. Its outgrows affecting communication to demography administrative services effectiveness as big as 13,18% and its rest as big as 86,82% regarded by unanalyzed other variable. Key word: Camat's communication, Ministering effectiveness